2013
DOI: 10.1371/journal.pone.0078467
|View full text |Cite
|
Sign up to set email alerts
|

Pistil Starch Reserves at Anthesis Correlate with Final Flower Fate in Avocado (Persea americana)

Abstract: A common observation in different plant species is a massive abscission of flowers and fruitlets even after adequate pollination, but little is known as to the reason for this drop. Previous research has shown the importance of nutritive reserves accumulated in the flower on fertilization success and initial fruit development but direct evidence has been elusive. Avocado (Persea americana) is an extreme case of a species with a very low fruit to flower ratio. In this work, the implications of starch content in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 57 publications
2
35
0
3
Order By: Relevance
“…This fifteen fold increase suggests that natural pollination is still a limiting factor in avocado production but also that, in spite of pollinating all the flowers of the inflorescence, still a low percentage of them are able to develop into fruits probably due to differences in flower quality at the time of anthesis (Alcaraz et al, 2010(Alcaraz et al, , 2013.…”
Section: Hand Pollination Vs Open Pollinationmentioning
confidence: 99%
See 1 more Smart Citation
“…This fifteen fold increase suggests that natural pollination is still a limiting factor in avocado production but also that, in spite of pollinating all the flowers of the inflorescence, still a low percentage of them are able to develop into fruits probably due to differences in flower quality at the time of anthesis (Alcaraz et al, 2010(Alcaraz et al, , 2013.…”
Section: Hand Pollination Vs Open Pollinationmentioning
confidence: 99%
“…For this reason, performing crosses that involve genotypes of the same floral group is difficult. Moreover, avocado is an extreme case of a species with a very low fruit to flower ratio, with less than 1% of the flowers produced able to set fruits due to a massive drop of flowers and developing fruitlets (reviewed in Alcaraz et al, 2013) making the development of progenies with high number of individuals difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Such effect may be most pronounced during the period of flowering and fruit set when carbohydrate demand is highest. Starch reserves were previously demonstrated be correlated to flower viability of several fruit trees including apricot [21], avocado [23, 24], and citrus [60]. In olives, Reale et al [27] showed that ovary and ovule starch levels were closely related to perfect flower development.…”
Section: Discussionmentioning
confidence: 99%
“…In general, flower carbohydrate reserves support pollen tube growth and early development of embryos [21] and therefore are thought to be significant enhancers of productivity [2224]. In olive, flowering induction does not seem to rely on carbohydrate reserves as shown by Stutte and Martin [25], using manipulation of light and CO 2 , and by Cherbiy-Hoffmann et al (2015), using manipulations of light intensity.…”
Section: Introductionmentioning
confidence: 99%
“…Studies performed in ovaries and styles of avocado and other crop species (Alcaraz et al 2013) yielded that at anthesis the cells of the style were rich in starch, and starch content decreased in the days following anthesis suggesting a role in nutritive reserves in flower fertilization. Also, the starch content in the pistil at anthesis could be a good indicator of flower quality because it was present in all flowers that developed into fruits.…”
Section: Heslopmentioning
confidence: 99%